Regional ecological security evaluation with subjective and objective weights model based on multi remote sensing observations - Jianzhong Lu; Jianshu Wang; Tianyao Liu; Lihua He; Ning Zhu; Mengyuan Yang; Xinbo Liu (Geo-spatial Information Science)
With the rapid development of economy and urban construction, urban ecological security protection has become a prominent issue in the development process. Territorial spatial planning and urban ecological monitoring urgently need the support of a scientific evaluation system of urban ecological security status. To respond the demand of ecological assessment, this study considers a variety of key ecological factors. A generalized assessment framework for ecological security is constructed. According to the data accessibility of the indicators and their representativeness. The 23 indicators centered on the elements of ecological environment change of water, soil, air, forest and grassland were divided into four tasks for detailed review: ecological health, ecological space, ecological economy and ecological life. As for weight allocation, to avoid the irrationality of the weights from the single method, we use a weight integration approach to integrate the subjective weights of the analytic hierarchy process (AHP) and the objective weights of the entropy weight method (EWM). Combining the above, the ecological security comprehensive index (ESCI) for evaluation was finally developed. The method was applied to assess the ecological security of Yichang (YC) in 2021. It was found that Xiling District, the core of the YC, had the highest ESCI, while Xiaoting and Zhijiang have the lowest. However, even Xiling still has room for improvement in terms of ecological space and ecological environment. All other cities also suffer from one or more lagging tasks. This framework reveals the general trend of the need to strengthen spatial and environmental construction in the developed areas, and the need to strengthen living and economic construction in the backward areas in YC. It can provide a comprehensive decision-making basis for ecological restoration decision-making and ecosystem management.